Pengaruh Kualitas Pelayanan dan Harga Terhadap Kepuasan Konsumen Pada Toserba Cempaka di Desa Celukan Bawang - Artana, Putu Yudi; Meitriana, Made Ary (Jurnal Pendidikan Ekonomi Undiksha, 2025)
This research aims to analyze the influence of service quality and price on consumer satisfaction at the Cempaka department store in Celukan Bawang village. The data source for this research is primary data. Primary data in this research is in the form of questionnaires obtained from respondents directly, namely Cempaka Department Store consumers. The sample selection technique in this research uses nonprobability sampling using accidental sampling because there is no fixed population size. This research used a sample of 130 respondents. Data analysis used SPSS version 23 software using descriptive analysis and multiple linear regression analysis. The research results show that service quality has a positive and significant effect on consumer satisfaction. Price has a positive and significant effect on consumer satisfaction. Service quality and price simultaneously have a positive and significant effect on consumer satisfaction.